Research on Visualization Development of Broadcast Programs Based on Big Data Analysis in Converged Media Environment. Issue 2 (October 2020) - Lin, Liya
Abstract: According to the data released by Saixin Media Research "data Broadcasting", the broadcast contact rate in China is 59.5%. Although in the era of media integration, the mobile Internet has some influence on the traditional media, but for broadcasting, it still has no less influence in its hands than in the past, and still maintains a steady upward trend. According to the relevant statistics, on the Internet, the audience on the Internet only ranks second behind the television media, followed by the traditional radio and newspaper traditional media broadcasting. In the process of continuous development and reform, it has not been eliminated by today's market, but has shown a trend of growth against the trend. It can be seen that radio programs that rely solely on sound communication and information consultation are in the process of the development of traditional media. There is still a very large audience. In the era of media development, traditional media is also absorbing a new generation of radio listeners through the means and technology of the new era, among which the visual development of broadcast programs is the focus of its reform and development.